Climatic variability as a principal driver of primary production in the southernmost subalpine Rocky Mountain lake - Anna Shampain; Jill S. Baron; Peter R. Leavitt; Sarah A. Spaulding (Arctic, Antarctic, and Alpine Research)
Mountain lakes are sensitive indicators of anthropogenically driven global change, with lake sediment records documenting increased primary production during the twentieth century. Atmospheric nutrient deposition and warming have been attributed to changes in other Western mountain lakes, however, the intensity of these drivers varies. We analyzed a sediment core representing a 270-year record from Santa Fe Lake, New Mexico, to constrain the southern margin of Rocky Mountain lakes and quantify patterns of change in lake biogeochemistry, production, and diatoms since 1750. Lake sediments were dated using 210Pb and analyzed for carbon (C), nitrogen (N), stable isotopes (δ13C, δ15N), diatoms, and phototrophic pigments. The abundance of cyanobacteria, purple sulfur-reducing bacteria, and diatom pigments were elevated during the stable conditions of the Little Ice Age; these phototrophic groups declined in the late 1800s and reached a minimum by 1950. From 1950 to 2020, sediments recorded an increased abundance of cryptophyte, diatom, and chlorophyte groups. The C and N (percentage dry mass) increased after 1950, whereas δ15N and δ13C values declined. Changes since the mid-twentieth century are contemporaneous with warming trends in the Southwest and modest deposition of atmospheric N. Our findings highlight the geographic variability of mountain lake responses to changing environmental conditions.